ChemInform Abstract: An Expedient Synthesis of β‐Acetamido‐ and β‐Benzamidocarbonyl Compounds via KAI(SO4)2·12H2O‐Catalyzed Three‐Component Coupling Reaction. Issue 16 (22nd April 2014) - Molla, Aniruddha; Hussain, Sahid
Abstract All products can be easily purified by recrystallization.